Knowledge Mapping of Cloud-Aerosol LIDAR and Infrared Pathfinder Satellite Observations Aerosol Research: A Visual Analysis Using CiteSpace - Chengyu Hu; Rui Zhang; Hwee San Lim; Yuanjun Zhang; Huan Du (Ocean-Land-Atmosphere Research)
The Cloud-Aerosol LIDAR and Infrared Pathfinder Satellite Observations (CALIPSO) satellite was launched in 2006 and concluded its mission in August 2023 after 17 years of dedicated service. This study conducted a bibliometric analysis on aerosol research using data from CALIPSO throughout its operational lifespan. The literature was organized into three primary categories: aerosol radiation characteristics and types, the spatiotemporal distribution of aerosols, and the spatial heterogeneity and driving factors. The software CiteSpace was used to analyze 2,131 research articles using data from CALIPSO to discern marked factors including keywords, research focal points, authors, journals, and affiliated institutions. The relationships among these factors were mapped to visualize past and future trends in this research domain. This study combined bibliometric analysis with a systematic literature review to present a comprehensive overview of how CALIPSO facilitated advances in aerosol research.